An Institutional History of the GED by Lois M. Quinn - (:unkn) unknown (My University, 2003)
This history of the development and promotion of the GED credential examines how a multiple choice test came to be the primary vehicle for educating high school non-completers and why so few adult high school completion programs model the Carnegie unit high school. The history examines the origin of the “general education development” curriculum advocated by the American Council on Education and the evolution of the Iowa Tests of Educational Development, the first GED test. It explores the attack on the Carnegie-unit high school by progressive educators during World War II and introduction of the GED test to promote their “testing for credit” alternative to classroom instruction. The GED test gained national recognition in the 1940s first as a college placement tool for enrolling veterans who had not completed high school. The history traces the American Council on Education’s efforts to promote use of the GED tests to measure “equivalency” to high school and the Council’s successful efforts to block states from issuing “wartime” high school diplomas for veterans who left high school to enter the service. Once the GED “high school equivalency” credential was accepted, the test publishers worked to market the GED test for non-veteran civilians and later for teenagers. Finally, the history examines the importance of marketing and government support to the GED testing program in the 21st century.
Keywords: GED; high school; truancy